2024
DOI: 10.3390/ijns10010006
|View full text |Cite
|
Sign up to set email alerts
|

Australian Public Perspectives on Genomic Newborn Screening: Risks, Benefits, and Preferences for Implementation

Fiona Lynch,
Stephanie Best,
Clara Gaff
et al.

Abstract: Recent dramatic reductions in the timeframe in which genomic sequencing can deliver results means its application in time-sensitive screening programs such as newborn screening (NBS) is becoming a reality. As genomic NBS (gNBS) programs are developed around the world, there is an increasing need to address the ethical and social issues that such initiatives raise. This study therefore aimed to explore the Australian public’s perspectives and values regarding key gNBS characteristics and preferences for service… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 57 publications
0
11
0
Order By: Relevance
“…Looking to the future, studies were also reported on the candidate conditions ALD [ 423 ] and DMD [ 424 ], and the Medical Services Advisory Committee recently announced their recommendations to add ALD and SCD to the Australian NBS panel [ 425 ].PD screening was proposed to the Australasian Standing Committee for Screening in 2018 but was not approved prompting publication of a report of PD screening activities in support of NBS [ 426 ]. The possibility of NBS for chromosome 15 imprinting disorders using genetic techniques [ 427 ] along with the knowledge and attitudes of Australian parents and health professionals towards genomic sequencing in NBS [ 428 ] and public perspectives on the risks, benefits, and preferences for implementation of gNBS [ 429 ]. A 2023 report notes that the addition of genomic sequencing into population-wide NBS will invariably expand the knowledge of treatable rare diseases, potentially benefiting health over a lifetime.…”
Section: Resultsmentioning
confidence: 99%
“…Looking to the future, studies were also reported on the candidate conditions ALD [ 423 ] and DMD [ 424 ], and the Medical Services Advisory Committee recently announced their recommendations to add ALD and SCD to the Australian NBS panel [ 425 ].PD screening was proposed to the Australasian Standing Committee for Screening in 2018 but was not approved prompting publication of a report of PD screening activities in support of NBS [ 426 ]. The possibility of NBS for chromosome 15 imprinting disorders using genetic techniques [ 427 ] along with the knowledge and attitudes of Australian parents and health professionals towards genomic sequencing in NBS [ 428 ] and public perspectives on the risks, benefits, and preferences for implementation of gNBS [ 429 ]. A 2023 report notes that the addition of genomic sequencing into population-wide NBS will invariably expand the knowledge of treatable rare diseases, potentially benefiting health over a lifetime.…”
Section: Resultsmentioning
confidence: 99%
“…Focus groups will explore public preferences and perspectives for (1) implementation of gNBS, (2) risks and benefits of gNBS and (3) use of data generated by gNBS as a lifetime resource and will involve qualitative exploration through facilitated discussion to elicit characteristics of gNBS delivery. 26 Outcomes from the focus groups will be used to inform the implementation phase of the study. The DCE surveys will elicit public preferences, values and priorities for gNBS to support the economic evaluation and implementation of gNBS in Australia.…”
Section: Methods and Analysismentioning
confidence: 99%
“…The preimplementation phase of the study involved extensive consultation with the public via focus groups 26 and DCE surveys. These have informed the design of the implementation phase.…”
Section: Methods and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Low [11] High [12] Relative public acceptability High [13] Mixed [14][15][16] Opportunities DBS 3 for retrospective epidemiological studies [17] Building on existing NBS workflows [18][19][20] Closer to phenotype [21,22] Ability to screen multiple conditions at once [23] Possibility of new biomarker discovery [24,25] Applicable to any condition type as a single test [26][27][28][29] Up-front molecular diagnosis [30][31][32] Lifetime re-use of data (WGS) [31,33] Enabling research into genedisease associations, treatment developments, population variation, and pharmacogenetic variation [31,[33][34][35][36] Challenges Feature characterization and data interpretation [37,38] May not be suitable for all condition types [23] Custom validation for each targeted condition [39][40][41] Need for sufficiently large validation cohorts [42] Consensus of which genes/variants to report [28,29,43] Possibility of identifying adultonset conditions/variants [44][45]…”
Section: Comparative Screening Costmentioning
confidence: 99%